Short-term exercise training reduces glycaemic variability and lowers circulating endothelial microparticles in overweight and obese women at elevated risk of type 2 diabetes. Issue 8 (14th September 2019) - Rafiei, Hossein; Robinson, Emily; Barry, Julianne; Jung, Mary Elizabeth; Little, Jonathan Peter
Abstract: Exercise is recognized as a frontline therapy for the prevention and treatment of type 2 diabetes (T2D) but the optimal type of exercise is not yet determined. We compared the effects of high-intensity interval training (HIIT) with moderate-intensity continuous training (MICT) for improvement of continuous glucose monitoring (CGM)-derived markers of glycaemic variability, and biomarkers of endothelial cell damage (CD31+ and CD62+ endothelial microparticles (EMPs)) within a population at elevated risk of developing T2D. Fifteen inactive overweight or obese women were randomized to 2 weeks (10-sessions) of progressive HIIT ( n = 8, 4–10X 1-min @∼ 90% peak heart rate, 1-min rest periods) or MICT ( n = 7, 20–50 min of continuous activity at ∼65% peak heart rate). Prior and three days post-training, fasting blood samples were collected. Both HIIT and MICT improved glycaemic variability as measured by CGM standard deviation (HIIT: 0.82 ± 0.39 vs. 0.72 ± 0.33 mmol/L; MICT: 0.82 ± 0.19 vs. 0.62 ± 0.16 mmol/L, pre vs. post) and mean amplitude of glycaemic excursions (MAGE; HIIT: 1.98 ± 0.81 vs. 1.41 ± 0.90; MICT; 1.98 ± 0.43 vs. 1.65 ± 0.48, pre vs. post) with no difference between groups. CD62+ EMPs were lower following HIIT (187.7 ± 65 vs. 174.9 ± 55, pre vs. post) and MICT (170 ± 60 vs. 160.3 ± 59, pre vs. post) with no difference between groups. There was no change in 24-h mean glucose or CD31+ EMPs. Two weeks of both HIIT or MICT similarly decreased glycaemic variability and CD62+ EMPs in overweight/obese women at elevated risk of T2D.